The role of early intervention in improving the level of activities and participation in youths after mild traumatic brain injury: a scoping review. (10th August 2017) - van Heugten, Caroline; Renaud, Irene; Resch, Christine
Mild traumatic brain injury in children can lead to persistent cognitive and physical symptoms which can have a negative impact on activities and participation in school and at play. Preventive treatment strategies are preferred because these symptoms are often not recognized and therefore not treated adequately. In this review clinical studies investigating interventions directed at pediatric mild traumatic brain injury are summarized, and clinical recommendations and directions for the future are provided. Results show that the literature is scarce and more high quality studies are needed. Information and education about the injury and its consequences are recommended, with additional follow-up consultation, including individualized advice and reassurance. The interventions should be family-centered and, ideally, the return to activity and participation should be graded and done step-by-step.